Efficient Deterministic Modelling of Three-Dimensional Rarefied Gas Flows (Communications in Computational Physics, 2012)
The paper is devoted to the development of an efficient deterministic framework for modelling of three-dimensional rarefied gas flows on the basis of the numerical solution of the Boltzmann kinetic equation with the model collision integrals. Theframework consists of a high-order accurate implicit advection scheme on arbitraryunstructured meshes, the conservative procedure for the calculation of the model collision integral and efficient implementation on parallel machines. The main applicationarea of the suggested methods is micro-scale flows. Performance of the proposed approach is demonstrated on a rarefied gas flow through the finite-length circular pipe.The results show good accuracy of the proposed algorithm across all flow regimes andits high efficiency and excellent parallel scalability for up to 512 cores.